Indigenous knowledge: A route to the infusion of sustainable development in education. - Mokhles, Ekbal Mohammed (AUC Knowledge Fountain, 2019)
Indigenous knowledge is the unique knowledge confined to a particular community, produced in order to cope with agro-ecological and socio-economic environments. The purpose of this study is to explore the perceptions of some educators around the issue of infusing indigenous knowledge embedded in communities such as Nubia in their school curricula similar to what other models in indigenous communities in countries such as Hawaii, Brazil and Australia did to reform their curricula. The research is based on the assumption that a culture- and place-based learning in Nubia can promote the infusion of indigenous knowledge. Foucault's theory of power and knowledge relation is adopted to show how indigenous knowledge could be viewed as a tool of empowerment to indigenous, "colonized" communities contributing to sustainable development. Nubians, within the framework of this theory, could be seen as colonized people seeking a space to practice their teachings and traditions. Unfortunately, this kind of space is denied in Egypt because Nubian students are subjugated to academic practices created by the "colonizing" public education system that refuses to absorb their local culture and heritage. This study uses a qualitative research design. Interviews with university professors, students and their parents on the possibility and means of integrating indigenous knowledge into curricula were conducted. There were 20 participants that included ten Nubian students, five Nubian parents of the same students and five academics in three different private universities in Egypt. Data from the interviews were analyzed based on Creswell's suggested steps for data analysis in qualitative research. The results indicate high perceptions of the importance of indigenous knowledge and the possibility of integrating it into curricula. The research indicates that the application and approaches towards education for sustainable development still need more thorough investigation in Egypt. Further attention should be given to integrating place-based learning and hands-on experience into educational curricula to encourage students to adapt to situations similar to those in real life.